2006
DOI: 10.1021/jf061286f
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Effects of Storage in Caviar from FarmedAcipenser transmontanusUsing Chemical, SEM, and NMR Methods

Abstract: The effects of storage at 4 degrees C on the quantity and quality of chemical components in the caviar from farmed Acipenser transmontanus have been analyzed by SEM, chemical methods, and NMR and MRI techniques. Particular attention has been focused on the lipid components, the distribution and mobility of which were strongly affected by the storage time. MRI and relaxation data indicated that lipids are endowed with two different mobility regimes, one slow (short T1) and one fast (long T1), both lengthening w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…However, there was no noticeable change for the moisture content in caviar with storage time from 0 to 11 months at −4°C, except in one month caviar sample, where a slight increase in moisture was observed. Similar results have been reported by others (Gussoni et al, ). The fluctuation in moisture content during storage was considered as the individual differences of caviar and the measurement of human error.…”
Section: Resultssupporting
confidence: 93%
“…However, there was no noticeable change for the moisture content in caviar with storage time from 0 to 11 months at −4°C, except in one month caviar sample, where a slight increase in moisture was observed. Similar results have been reported by others (Gussoni et al, ). The fluctuation in moisture content during storage was considered as the individual differences of caviar and the measurement of human error.…”
Section: Resultssupporting
confidence: 93%
“…); among fatty acids, oleic acid is the dominant and eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are particularly abundant (Gussoni et al . ; Caprino et al . ; Intarasirisawat et al .…”
Section: Caviar and Aquaculture: The Bright Side Of The Moonmentioning
confidence: 99%
“…It is very well known that fish roe and particularly caviar contains high amounts of proteins (Al-Holy & Rasco 2006) and lipids. The average protein content of caviar is about 30%, and fat ranges from 11% to 27% (wet weight) Gessner et al 2008;Mol & Turan 2008;Wirth et al 2002;Hamzeh et al 2015); among fatty acids, oleic acid is the dominant and eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are particularly abundant (Gussoni et al 2006;Caprino et al 2008;Intarasirisawat et al 2011;Wang et al 2012). While proteins play a minor role in the definition of caviar quality, lipids, in particular fatty acids, noticeably influence caviar taste, being off-flavours mainly originated by lipophilic compounds.…”
Section: Functional Plasticity: the Effects Of Sturgeon Farming On Camentioning
confidence: 99%
See 1 more Smart Citation
“…Other processing factors affect the final texture, colour and quality of caviars, including processing temperature, inappropriate dehydration or curing protocols and excessive lipid removal (Gessner et al 2002b;Al-Holy et al 2005b). Gussoni et al (2006) studied the effect of storage at 4°C on the levels of chemical components in caviars from farmed white sturgeon and showed that lipid hydrolysis took place during the caviar storage after 4 months and was faster in unsalted compared with salted roe indicative of enzymatic activity likely to be of microbial origin. Shin et al (2010) studied the storage stability of caviars from white sturgeon and indicated that compositional factors (i.e.…”
Section: Processing Techniques and Storagementioning
confidence: 99%